أبو المؤرج ودوره الفقهي من خلال مدونة أبي غانم الخراساني - المعمري, علي بن محمد بن سليمان (كلية العلوم الشرعية, 2001)
Keywords: Foi -- Traité -- 19e siècle

جوابات الشيخ موسى بن علي ( ت 230) هـ في باب الطهارات و الصلاة جمعا وترتيبا و دراسة - العزري, سيف بن حمد بن سيف (كلية العلوم الشرعية, 2001)
Keywords: الأحكام (فقه إسلامي)

الوحدة الإسلامية في فكر رواد الإصلاح الإباضية في العصر الحديث - الحجري, محمد بن راشد بن سعيد (كلية العلوم الشرعية, 2001)
Keywords: Réformisme

الحركة الإصلاحية الإسلامية بزنجبار منذ بداية القرن الرابع عشر الهجري إلى العصر الحاضر - موسى, نوح عثمان (كلية العلوم الشرعية, 2001)
Keywords: Réformisme -- Zanzibar

الشيخ نور الدين السالمي حياته وآثاره ومواقفه الإصلاحية والسياسية - شريفي, مصطفى بن محمد (جامعة الجزائر, 2001)
Keywords: Réformisme -- Oman

مرويات جابر بن زيد في مصادر الحديث السنية والإباضية 18-93هـ دراسة نماذج - حاج أمحمد, قاسم (جامعة الجزائر, 2001)
Keywords: Hadith -- Ibadisme

‏عمالة المرأة في البيت ‏بين التنشئه الاجتماعية والمستوى التعليمي دراسة ميدانية في منطقة غرداية - موسى المال, خديجة; قباني, مسعودة; بن عبد الرحمان, نفيسة (المركز الجامعي بغرداية, 2001)
Keywords: Enseignement -- Mzab

‏الميزابيون و التماسك الاجتماعي: دراسة ميدانية للميزابيين القيمين بالعاصمة - باجو, عبد الرحمان بن صالح; ابن ياحي, حمزه بن إبراهيم (جامعة الجزائر, 2001)

محمد بن سليمان ابن ادريسو ومنهجه في تفسير القرآن (1228-1313هـ) - امعيز الحاج أحمد, مصطفى بن محمد بن أحمد (معهد الحياة, 2001)

Les ambiances sonores en sites traditionnels : vers une identité sonore des villes mozabites Ghardaia - Ben Usgen - El Atteuf - Hamani, Dalil Omar (Université de Nantes, 2001)
Keywords: Urbanisme -- Mzab

دور الصحافة العربية بتونس في تفعيل الوعي الوطني 1860-1914 - حسن, اللولب حبيب (جامعة الجزائر, 2001)

تعليم البنات في ميزاب بين الأصالة والحداثة: دراسة لميكانيزمات التغيير في الوقع الإجتماعي - مرموري, بشير (جامعة الجزائر, 2001)
Keywords: Enseignement -- Mzab

إسماعيل بن موسى الجيطالي وآراؤه الكلامية - باباواعمر, خضير بن بكير (جامعة الجزائر, 2001)
Keywords: Jayṭālī, Ismāʿīl b. Mūsà (13..-1350)

‘Native Arts’ and Empire: The ‘Renovation’ of Artisanal Production in French Colonial North Africa, 1900-1939 - Mokhiber, James Pardee (Johns Hopkins University, 2001)

Evolution and Change: Town and Country in Late Antique North Africa - Leone, Anna (University of Leicester, 2001)

المجتمع المزابي وتدريس اللغة الأمازيغية: دراسة ميدنية في مدينة القرارة بمزاب - أوجانة, حميد (جامعة الجزائر, 2001)
Keywords: Berbérisme -- Mzab

Regional politics in the developing World : the case of the Arabian Peninsula Yemen, Saudi Arabia, Oman - Manea, Elham (University of Zürich, 2001)

The Qur'anic Exchange of the Self in the Poetry of Shurāt (Khārijī) political identity 37-132 A.H./657-750 A.D. - Higgins, Annie C. (University of Chicago, 2001)
Keywords: poésie kharijite

الإنتاج الإباضي في علم التفسير - الشيباني, سلطان بن مبارك (معهد العلوم الشرعية, 2001)

al-Fikr al-Iṣlāḥī ʿinda ‘l-Shaykh Abī ‘l-Yaqẓān - Gharāba, Zakiyya Manzal (Jāmiʿat al-Amīr ʿAbd al-Qādir, 2001)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973)

The Omani siyar as a literary genre and its role in the political evolution and doctrinal development of Eastern Ibadism, with special reference to the epistles of Khwarizm, Khurasan and Mansura - Salimi, Abdulrahman al- (Durham University, 2001)

Ismāʿīl b. Mūsà al-Jayṭālī wa-Ārā’uhu al-Kalāmiyya - Bābāwāʿumar, Khaḍīr b. Bakīr (Université d'Alger, 2001)
Keywords: Jayṭālī, Ismāʿīl b. Mūsà (13..-1350)

الفكر العقدي عند الاباضية حتى نهاية القرن الثاني الهجري - الوهيبي, مسلم بن سالم (جامعة الأزهر, 2001)
Keywords: Foi -- Ibadisme

الأغنية النسائية بجزيرة جربة - النجاع, عبد الكريم (المعهد العالي للموسيقى, 2001)
Keywords: Musique -- Djerba

رواة المرجئة والقدرية والخوارج في الكتب الستة واقوال علماء الجرح والتعديل فيهم : دراسة نقدية تحليلية - بخيت, إسماعيل عبدالرحيم (جامعة القرآن الكريم والعلوم الإسلامية, 2001)
Keywords: Kharijisme

أثر الفكر الأباضي في الشعر العماني في القرنين الثالث عشر والرابع عشر الهجريين - السليمي, محمود بن مبارك بن حبيب (الجامعة الاردنية, 2001)
Keywords: Poésie -- Oman

الرخص في الفقه الإباضي - الشعيلي, خلفان بن سنان (جامعة الزيتونة, 2001)
Keywords: Fiqh

Tourismus auf Djerba / Tunesien: zur beziehung zwischen touristen und lokaler bevolkerung - Khiari Loch, Ina (Universität Bayreuth, 2001)
Keywords: Tourisme -- Djerba

Manifestations of religious individualism in Kharijite poetry - Sullivan, Mark Stover (University of Texas, 2001)
This dissertation deliberates manifestations of religious individualism Kharijite poetry during the Umayyad era, AD. 661 to 750. The opening chapters discuss various inadequacies in the study of Umayyad poetry in general and Kharijite poetry in particular that often concentrate upon the perceived static nature of form and neglect significant changes that occur in the content and function of poetry. Chapters four and five examine aspects of Kharijite ideology that paved the way for the development of religious individual. Chapter six through ten discuss the various manifestations of this nascent religious individualism in Kharijite poetry. The dissertation argues that specific perspectival shifts that occur predominantly in elegy mark an important departure from Classical and Medieval Arabic poetry in general. In a significant number of Kharijite elegies, the poets' focus on the self replaced or superseded the ritualistic mourning for the martyr, the traditional subject of the elegy during this historical period. Elegy became increasingly a platform and vehicle for self examination, self-reflection and religious self-scrutiny. These characteristics signify the emergence of a nascent religious individualism in Kharijite poetry.
Keywords: Kharijisme

Le parler arabe des Juifs De Djerba. Étude linguistique - Ben Mbarek, Hala (Inalco, 2001)
Keywords: Linguistique

Fonctions et usages de la photographie en anthropologie. Des cafés bellevillois (Paris XXe) à l’île de Djerba (Tunisie): échanges entre des femmes juives d’origine tunisienne et une anthropologue-photographe - Conord, Sylvaine (Université de Paris X, 2001)
Keywords: Judaïsme -- Djerba

Djerba : impact des mutations engendrées par l’implantation d’un pôle touristique sur une île tournée vers l’émigration internationale - Bernard, Élise (Université de Poitiers, 2001)
Keywords: Démographie -- Djerba